American Foreign Policy In A Globalized World - FORSYTHE, P. David (Routledge, 2006)
In this volume, several leading foreign policy and international relations experts consider the long term prospects and implications of US foreign policy as it has been shaped and practiced during the presidency of George W. Bush.